On specimen killing in the era of conservation crisis - A quantitative case for modernizing taxonomy and biodiversity inventories. - Patrick O Waeber; Charlie J Gardner; Wilson R Lourenço; Lucienne Wilmé (PLoS ONE, 2017)
Background to the work For centuries taxonomy has relied on dead animal specimens, a practice that persists today despite the emergence of innovative biodiversity assessment methods. Taxonomists and conservationists are engaged in vigorous discussions over the necessity of killing animals for specimen sampling, but quantitative data on taxonomic trends and specimen sampling over time, which could inform these debates, are lacking. Methods We interrogated a long-term research database documenting 2,723 land vertebrate and 419 invertebrate taxa from Madagascar, and their associated specimens conserved in the major natural history museums. We further compared specimen collection and species description rates for the birds, mammals and scorpions over the last two centuries, to identify trends and links to taxon descriptions. Results We located 15,364 specimens documenting endemic mammals and 11,666 specimens documenting endemic birds collected between 1820 and 2010. Most specimens were collected at the time of the Mission Zoologique Franco-Anglo-Américaine (MZFAA) in the 1930s and during the last two decades, with major differences according to the groups considered. The small mammal and bat collections date primarily from recent years, and are paralleled by the description of new species. Lemur specimens were collected during the MZFAA but the descriptions of new taxa are recent, with the type series limited to non-killed specimens. Bird specimens, particularly of non-passerines, are mainly from the time of the MZFAA. The passerines have also been intensely collected during the last two decades; the new material has been used to solve the phylogeny of the groups and only two new endemic taxa of passerine birds have been described over the last two decades. Conclusions Our data show that specimen collection has been critical for advancing our understanding of the taxonomy of Madagascar's biodiversity at the onset of zoological work in Madagascar, but less so in recent decades. It is crucial to look for alternatives to avoid killing animals in the name of documenting life, and encourage all efforts to share the information attached to historical and recent collections held in natural history museums. In times of conservation crisis and the advancement in digital technologies and open source sharing, it seems obsolete to kill animals in well-known taxonomic groups for the sake of enriching natural history collections around the world.